PENGARUH SOSIAL MEDIA TIKTOK TERHADAP GAYA KOMUNIKASI REMAJA DI KOTA BATAM - Encah Herlina; Riswandi Riswandi (SCIENTIA JOURNAL, 2026)
The use The rapid growth of TikTok as a social media platform has significantly influenced communication patterns among adolescents in the digital era. TikTok is not only used for entertainment but also serves as a medium for self-expression and social interaction, which may shape users’ communication styles. This study aims to examine the effect of TikTok usage on adolescents’ communication styles in Batam City. The research employed a quantitative approach using a survey method. A total of 100 respondents aged 11–21 years were selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression with SPSS version 25. The results indicate that TikTok usage has a positive and significant effect on adolescents’ communication styles, with a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.490 suggests that TikTok usage accounts for 49% of the variance in adolescents’ communication styles, while the remaining 51% is influenced by other factors. These findings support the Uses and Gratifications Theory, which emphasizes active media use to fulfill communication needs. Keywords: TikTok, Social Media, Communication Style, Adolescents